(untitled) (International Journal of Food and Nutritional Sciences, 2022)
As the conventional irreversible logic dissipates power for losing bits of information, computing engines has to be designed that do not require energy dissipation but only if computation is done logically reversible. Hence, research on reversible logic has been extensively increased now-a-days for its application in Quantum Computing, nanotechnology; QCA and Low power VLSI etc. In this paper, we have realized a Quantum Cost efficient Reversible RAM (RRAM) with a new 3x3 Reversible Gate named Modified Fredkin (MF). While approaching for RRAM we have also proposed a reversible D Flip-flop with minimum quantum cost (Qc), a write enabled reversible master slave D Flip-flop & a (i*2^i) reversible decoder which has outperformed the existing designs in terms of quantum cost, ancilla & garbage outputs. We also have analyzed the architectures in terms of logical depth (worst case delay), hardly addressed in available literature.